Entrepreneurial Education as a Strategy for Global Competitiveness: Entrepreneurship Challenge in Puerto Rico - Moraima De Hoyos Ruperto; Carmen I. Figueroa Medina (Centro de Investigaciones Comerciales e Iniciativas Académicas, 2011)
Entrepreneurial education is important as a diffusion mechanism to foster mind-sets, skills, and behaviors on the entrepreneurship context in Puerto Rico. Entrepreneurial challenges were denoted by interviewing governmental, private and civic sectors¿ leaders as well entrepreneurs. Qualitative analysis demonstrates a successful entrepreneurial strategy should be anchored in an inter organizational process that could build up the adequate entrepreneurial mindset through a formal interdisciplinary educational curriculum. Results suggest the necessity of change from the traditional business education hub to an entrepreneurial education able to develop creative thoughts as a strategy for global competitiveness and sustainable entrepreneurial growth.